THE ROLE OF THE ENTREPRENEURSHIP SCHOOL PROGRAM (SPW) IN REDUCING UNEMPLOYMENT RATES IN INDONESIA THROUGH STUDENTS' CHARACTER AND ENTREPRENEURSHIP SKILLS DEVELOPMENT - Andrianto, Ahmad; Yusuf, Yusuf; Sudarmiatin, Sudarmiatin; Firmansyah, Risky (Nusantara Economics and Entrepreneurships Journals, 2024)
This study presents a case study of an entrepreneurship program in a vocational high school, namely the Entrepreneurship Producing School (SPW), which aims to implement entrepreneurship education and can improve entrepreneurial skills and develop students' entrepreneurial character. The method used in this study is descriptive qualitative, involving interviews and observations to collect data from mentor teachers and students involved in the SPW program. Social cognitive theory is applied to understand how students' entrepreneurial intentions and success are influenced by internal and external factors, including educational environmental support. The results show that the SPW program has succeeded in improving students' entrepreneurial skills, with many students being able to run businesses and achieve significant turnover. These findings emphasize the importance of ongoing educational support and strategies to increase students' motivation in entrepreneurship, in order to contribute to reducing unemployment in Indonesia